Evaluation of visual performance and eye movements in patients with blue light-filtering intraocular lenses versus ultraviolet light-filtering intraocular lenses - Liu, Yan; Ren, Xiaotong; Wan, Yu; Yang, Luling; Zhang, Rong; Li, Xuemin (Frontiers in Neuroscience, 2023)
Background Eye movement plays an important role in visual perception and provides essential visual information for everyday tasks. Our previous study indicated that the visual performance and eye movement pattern were impaired in age-related cataract patients and could be improved after cataract surgery, but the impact of different intraocular lens (IOL) types was obscure. Previous studies found that blue light might affect the eye movement pattern and cognitive function. In this study, we explored the visual performance and eye movement pattern in post-cataract surgery patients implanted with blue light-filtering IOLs or ultraviolet (UV) light-filtering IOLs to further understand the impact of different types of IOLs on and daily visual performance and eye movement pattern and to help ophthalmologists and patients make the personalized option of IOL types in future. Methods Patients after both-eye cataract surgeries were included in this study. Eye movement behaviors were automatically recorded by an eye tracker while performing three performance-based everyday tasks (non-social object search, face recognition, and reading). Visual performance and eye movement parameters were compared between participants with blue light-filtering IOLs and UV light-filtering IOLs. The correlation between visual performance and eye movement parameters was explored to determine which eye movement parameters had a significant influence on visual performance outcomes. Results A total of 30 patients (16 with blue light-filtering IOLs and 14 with UV light-filtering IOLs) were included. In this study, we found that the eye movement pattern was slightly different with these two IOLs: during non-social object visual search task, time to first fixation and fixation counts before first fixation were notably increased in yellow-tinted blue light-filtering IOL patients. During reading task, a higher total fixation count was also found in blue light-filtering IOL patients. However, the visual performance of these two IOLs was close, except for a quicker search of the target object with clear UV light-filtering IOLs. Conclusion Both blue light-filtering and UV light-filtering IOLs were able to successfully restore visual function and yield satisfactory outcomes after cataract surgery. Although subtle, yellow-tinted IOLs did have a slight but significant impact on visual performance and the eye movement pattern of elderly patients when handling everyday tasks.